The Maya Temple-Palace of Santa Rosa Xtampak, Mexico Large Size Maps and Plans - Hohmann, Hasso (Verlag der Technischen Universität Graz, 2017)
The publication presents a detailed architectural documentation and reconstruction of the impressive 1,275-years-old, three-story temple-palace of Santa Rosa Xtampak in Campeche, Mexico. The analysis of the 17 m high 50-room structure with two inner staircases revealed unusual construction principles and serious static problems preventing a planned high roof comb. The publication provides several architectural indications for different functions of the structure, which might also be used to study functions at other Maya buildings.Publication see: http://e-book.fwf.ac.at/o:1106